The Role of Anxiety Scales and Serum Copeptin Levels in Determining the Preprocedure Anxiety Status of Patients Who Undergo Fiberoptic Bronchoscopy and Endobronchial Ultrasonography - Sümeyye Kodalak Cengiz; Canan Yılmaz; Ahmet Selim Yurdakul (International Journal of Clinical Practice)
Introduction. Fiberoptic bronchoscopy (FOB) and endobronchial ultrasonography (EBUS) are safe and frequently used minimally invasive procedures. However, the decision to undergo an interventional procedure causes anxiety development and negative consequences in the individual. Objective. To determine the role of the State-Trait Anxiety Inventory (STAI), Beck Anxiety Inventory (BAI), visual analog scale (VAS), and serum copeptin levels, their sensitivity, specificity, and the correlation between them in the anxiety levels of patients before undergoing FOB and EBUS. Method. A total of 219 patients who were scheduled to undergo FOB/EBUS were included in this prospective observational study. Demographic data were recorded. Patients’ anxiety levels before the procedure were evaluated using STAI-SA, STAI-TA, BAI, and VAS. Copeptin levels were measured before and after the procedure. Results. Patients were moderately anxious according to STAI-SA, STAI-TA, and VAS and were mildly anxious according to the BAI. Women and patients aged under 65 years were significantly more anxious. All scales were positively correlated. Serum copeptin levels before the procedure were 5.8 ± 4.8 and 4.3 ± 3.9 ng/mL afterwards, with a significant difference between them. The specificity and sensitivity of VAS were found to be the highest. Conclusion. All anxiety scales are correlated with each other, and we recommend VAS as a powerful alternative for determining anxiety levels in terms of easier understanding and implementation. Serum copeptin levels before the procedure were significantly higher than afterwards and may be used as a potential biomarker for preprocedural anxiety.